The approach of socioscientific issues through children’s literature: a survey about the importance given by pre-service teachers - Almeida, António (2022)
The approach of socioscientific issues, some of them controversial, has led teachers to look for educational resources that help them in this task. Children’s literature has been one of this resources, as several books have been incorporating these issues. Some emerging issues are those related to sexuality and parental reality as well as the ones addressing environmental themes.